2018
DOI: 10.1016/j.ijpharm.2018.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Injectable long-acting human immunodeficiency virus antiretroviral prodrugs with improved pharmacokinetic profiles

Abstract: While highly active antiretroviral therapy (HAART) has significantly reduced mortality rates in patients with human immunodeficiency virus type 1 (HIV-1), its efficacy may be impeded by emergence of drug resistance caused by lack of patient adherence. A therapeutic strategy that requires infrequent drug administration as a result of sustained release of antiretroviral drugs would put less burden on the patient. Long-acting antiretroviral prodrugs for HIV therapy were synthesized through modification of the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The palmitic acid prodrug of DTG has been formulated into biodegradable microparticles [ 74 ], and PK evaluation in rabbits (SC injection, 30 mg/kg) showed that the IC 90 of DTG was maintained for >3 months. LA polyunsaturated fatty-acid prodrugs of FTC and elvitegravir (EVG) exhibited superior antiviral activities in HIV replication tissue models and LA characteristics in mice [ 75 ].…”
Section: Approaches To Improving Existing Arvs For La Hiv Preventionmentioning
confidence: 99%
“…The palmitic acid prodrug of DTG has been formulated into biodegradable microparticles [ 74 ], and PK evaluation in rabbits (SC injection, 30 mg/kg) showed that the IC 90 of DTG was maintained for >3 months. LA polyunsaturated fatty-acid prodrugs of FTC and elvitegravir (EVG) exhibited superior antiviral activities in HIV replication tissue models and LA characteristics in mice [ 75 ].…”
Section: Approaches To Improving Existing Arvs For La Hiv Preventionmentioning
confidence: 99%
“…However, the majority of the investigated antiretroviral agents are not well suited for formulation as long-acting injectables due to suboptimal physicochemical properties limiting their formulation as conventional drug suspensions, as well as insufficient antiviral potency resulting in high monthly dosing requirements. The identification of single vehicles capable of dissolving multiple drugs for solution-based long-acting injections provides a number of hurdles, especially when attempting to overlay various partition coefficients to maintain the dose ratios over extended periods [ 7 , 8 , 9 ]. It is thus clear that novel formulation approaches capable of achieving extended-duration pharmacokinetics for molecules of diverse physicochemical properties, at practical injection volumes and with a limited number of injections, are highly desirable.…”
Section: Introductionmentioning
confidence: 99%